Effect of aerobic exercise on the atherogenic index of plasma in middle-aged Chinese men with various body weights. (1st March 2017) - Shen, Shiwei; Lu, Yun; Dang, Yingjie; Qi, Huajin; Shen, Zhenhai; Wu, Liuxin; Li, Feng; Yang, Chengjian; Qiang, Dongchang; Yang, Yan; Shui, Kedong; Bao, Yanying
Abstract: Objective: The aim of this study was to examine the correlation between aerobic exercise and the atherogenic index of plasma (AIP) in middle-aged Chinese men stratified by body weight. Methods: A cross-sectional study, which recruited 26, 701 middle-aged Chinese men undergoing health examinations in our hospital from 1st January 2014 to 30th June 2015 was performed, and the associations between body weight and AIP, and aerobic exercise and AIP were evaluated. Results: The mean AIP levels were − 0.016 ± 0.305, 0.138 ± 0.3171 and 0.211 ± 0.3243 in normal weight, overweight and obese subjects, respectively, and appeared to rise with body weight. Significantly higher AIP levels were observed in subjects with a weekly aerobic exercise period ≥ 90 min than in those with a weekly aerobic exercise period < 90 min, and the mean AIP levels were − 0.038 ± 0.3015, 0.117 ± 0.3182 and 0.192 ± 0.3209, and were 0.003 ± 0.3067, 0.156 ± 0.3149 and 0.225 ± 0.3263 in normal weight, overweight and obese men with a weekly aerobic exercise period ≥ 90 min and < 90 min, respectively. In addition, aerobic exercise significantly reduced AIP after adjustment for age, systolic blood pressure, diastolic blood pressure, body mass index (BMI), fasting blood glucose and uric acid. Conclusions: Lowering body weight and/or increasing aerobic exercise time may reduce AIP, and lowering body weight results in a greater reduction in AIP than aerobic exercise. Weight control combined with increased aerobic exercise time may cause a synergistic effect on the reduction of AIP.